2021
DOI: 10.1111/trf.16268
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between SARS‐COV‐2 antibody screening by immunoassay and neutralizing antibody testing

Abstract: Background The efficacy of convalescent plasma (CP), an alternative for the treatment of COVID‐19, depends on high titers of neutralizing antibodies (nAbs), but assays for quantifying nAbs are not widely available. Our goal was to develop a strategy to predict high titers of nAbs based on the results of anti‐SARS‐CoV‐2 immunoassays and the clinical characteristics of CP donors. Study Design and Methods A total of 214 CP donors were enrolled and tested for the presence o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 31 publications
9
32
0
Order By: Relevance
“…12 , 13 In the current study we used the Euroimmune ELISA assay to quantify SARS-CoV-2 antibody level as it was reported to highly correlate with the neutralizing antibody assay. 14 …”
Section: Discussionmentioning
confidence: 99%
“…12 , 13 In the current study we used the Euroimmune ELISA assay to quantify SARS-CoV-2 antibody level as it was reported to highly correlate with the neutralizing antibody assay. 14 …”
Section: Discussionmentioning
confidence: 99%
“…Only one individual among the questionnaire responders was previously diagnosed with a COVID-19 infection and was excluded. In addition, no quantitative analysis of neutralizing antibodies was performed, however, several studies showed a positive correlation between IgG against the receptor-binding domain (RBD) and neutralizing antibody titers [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same antibodies are also present in individuals once the SARS‐CoV‐2 infection is resolved, at levels that depend on the duration and severity of clinical symptoms 4 . The efficacy of passive antibody therapy has been associated with the concentration of nAbs in the convalescent plasma (CP) of recovered patients 5,6 . Thus, it would be useful to immediately identify donors with high nAbs titres.…”
Section: Figurementioning
confidence: 99%